PENGARUH PEMANFAATAN MEDIA VIDEO PEMBELAJARAN DAN PARTISIPASI SISWA DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR IPAS DI KELAS IV SD NEGERI SULIT AIR KECAMATAN X KOTO DIATAS KABUPATEN SOLOK - Misri Yance; Jamaris Jamna; Jaka Warsihna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of learning video utilization and student participation on learning outcomes of fourth grade students of SDN 05 Gando Sulit Air. The research method used a quantitative approach with a pseudo-experimental design, involving 12 students as an experimental class (video-based learning) and 18 students as a control class by not using learning video media. Data were collected through observation of student participation and learning outcome tests, then analyzed using normality test (Shapiro-Wilk), homogeneity test (Levene's Test), independent t-test, and Pearson correlation. The results showed: (1) There is a significant difference in learning outcomes between the experimental class (mean=93) and the control class (mean=72) with t-count=8.45 (p=0.000); (2) Student participation of the experimental class (mean=83) is significantly higher than the control class (mean=73) with t-count=7.12 (p=0.000); (3) There is a strong relationship between student participation and learning outcomes (r= 0.82; p=0.001). Regression analysis showed a combined contribution of 78% (R² = 0.78). The conclusion of this study proves that the use of learning videos significantly improves students' participation and learning outcomes. The findings support Mayer's (2009) multimedia learning theory and recommend the use of videos as an innovative learning medium in elementry schools.